2007
DOI: 10.1021/jf071938f
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 Extract of Cinnamomum zeylanicum: Chemical Characterization and Antityrosinase Activity

Abstract: The volatile oil of the bark of Cinnamomum zeylanicum was extracted by means of supercritical CO2 fluid extraction in different conditions of pressure and temperature. Its chemical composition was characterized by GC-MS analysis. Nineteen compounds, which in the supercritical extract represented >95% of the oil, were identified. (E)-Cinnamaldehyde (77.1%), (E)-beta-caryophyllene (6.0%), alpha-terpineol (4.4%), and eugenol (3.0%) were found to be the major constituents. The SFE oil of cinnamon was screened for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 37 publications
(37 reference statements)
6
59
2
6
Order By: Relevance
“…According to studies carried out by several investigators, the major component of cinnamon essential oil was cinnamaldehyde in the range of 44% -97% (7,17,18). Marongiu et al (2007) (19) and Fei et al (2011) (2) reported that the main component of cinnamon essential oil was trans-cinnamaldehyde (77.1% and 77.3%, respectively). These findings are in agreement with the results of our study, since the concentration of cinnamaldehyde was found to be 79.74% in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies carried out by several investigators, the major component of cinnamon essential oil was cinnamaldehyde in the range of 44% -97% (7,17,18). Marongiu et al (2007) (19) and Fei et al (2011) (2) reported that the main component of cinnamon essential oil was trans-cinnamaldehyde (77.1% and 77.3%, respectively). These findings are in agreement with the results of our study, since the concentration of cinnamaldehyde was found to be 79.74% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The higher resistance of Gram-negative bacteria than Gram-positive bacteria to essential oils is possibly owing to differential membrane structure of these bacteria. Gram-negative bacteria have an outer phospholipid membrane that acts as a barrier and renders the membrane impermeable to lipophilic constituents (19,20). In Gram-positive bacteria, direct contact between hydrophobic components and the phospholipid layer of the cell membrane occurs owing to lack of an outer phospholipid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, C. osmophloeum is also used as a replacement spice for C. cassia (13). One of the main constituents of essential oil obtained from C. zeylanicum termed (E)-cinnamaldehyde has an antityrosinase activity (14), whereas cinnamaldehyde is the main compound accountable for this activity (15). The purpose of this paper is to review recent researches in the therapeutic efficient of cinnamon particularly on high BP disease, and patients with prediabetes and type 2 diabetes mellitus (T2DM).…”
Section: The Therapeutic Effect Of Cinnamon On Hypertensionmentioning
confidence: 99%
“…The low antimicrobial effect of coating with EWPP, and EWPP containing EO T at different concentrations, on E. coli O157:H7 was associated with the ability of E. coli O157:H7 to grow in mediums with a low pH (pH < 3.6) and its resistance to acidity [41]. Furthermore, E. coli O157:H7 contains an outer phospholipid membrane that acts as a barrier and renders the membrane impermeable to lipophilic compounds [42], and studies have shown that this membrane protected the bacteria against the essential oils [43].…”
Section: Microbiological Propertiesmentioning
confidence: 99%